2011
DOI: 10.1007/s13205-011-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor-based bioremediation of hydrocarbon-polluted Niger Delta marine sediment, Nigeria

Abstract: Crude oil-polluted marine sediment from Bonny River loading jetty Port Harcourt, Nigeria was treated in seven 2.5 l stirred-tank bioreactors designated BNPK, BNK5, BPD, BNO3, BUNa, BAUT, and BUK over a 56-day period. Five bioreactors were biostimulated with either K2HPO4, NH4NO3, (NH4)2SO4, NPK, urea or poultry droppings while unamended (BUNa) and heat-killed (BAUT) treatments were controls. For each bioreactor, 1 kg (wet weight) sediment amended with 1 l seawater were spiked with 20 ml and 20 mg of crude oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…Effect of different amount of organic fertilizer (cattle dung + pig dung+ poultry droppings) on TPH biodegradation were investigated at the same condition of inorganic NPK fertilizer and activated carbon (run numbers 6 and 8, and run numbers 10 and 12) and the results showed that addition of organic fertilizer (cattle dung + pig dung + poultry droppings) can enhance the bioremediation process of soil contaminated with crude oil. This is in agreement with the observations of Ibiene et al (2011), Nduka et al (2012, Chikere et al (2012) and Obiakalaije et al (2015) who respectively used poultry droppings and/or cow dung as organic fertilizer (biostimulation agents) in the remediation of petroleum hydrocarbon contaminated environment. Agarry et al (2010) and Agarry et al (2013b) had in their previous studies also reported the enhancement of bioremediation in soil contaminated with petroleum hydrocarbons using cow dung, pig dung, poultry dung as well as the mixture of cow dung and pig dung, respectively.…”
Section: Soil and Animal Wastes Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…Effect of different amount of organic fertilizer (cattle dung + pig dung+ poultry droppings) on TPH biodegradation were investigated at the same condition of inorganic NPK fertilizer and activated carbon (run numbers 6 and 8, and run numbers 10 and 12) and the results showed that addition of organic fertilizer (cattle dung + pig dung + poultry droppings) can enhance the bioremediation process of soil contaminated with crude oil. This is in agreement with the observations of Ibiene et al (2011), Nduka et al (2012, Chikere et al (2012) and Obiakalaije et al (2015) who respectively used poultry droppings and/or cow dung as organic fertilizer (biostimulation agents) in the remediation of petroleum hydrocarbon contaminated environment. Agarry et al (2010) and Agarry et al (2013b) had in their previous studies also reported the enhancement of bioremediation in soil contaminated with petroleum hydrocarbons using cow dung, pig dung, poultry dung as well as the mixture of cow dung and pig dung, respectively.…”
Section: Soil and Animal Wastes Parameterssupporting
confidence: 92%
“…Similar observations have been reported (Chorom et al, 2010;Chikere et al, 2012;Ogunleye, 2012a, 2012b). Thus, the observed results seems to suggest that high nutrient amendment dosage can accentuate the rate of initial petroleum hydrocarbon biodegradation and then reduce the remediation period of environment contaminated with crude oil.…”
Section: Soil and Animal Wastes Parameterssupporting
confidence: 89%
“…For example, Vullo et al (2008) isolated bacteria which were resistant to both Zn and Cd. Chikere et al (2012) reported bioreactor-based bioremediation of hydrocarbonpolluted marine sediments biostimulated with either K 2 HPO 4 , NH 4 NO 3 , (NH 4 ) 2 SO 4 , NPK, urea or poultry droppings across the Bonny river, Port Harcourt, Nigeria.…”
Section: Bioremediation Of Multi-metal Waste Sites/radionuclidesmentioning
confidence: 99%
“…These hydrocarbons and alkanes have been considered as priority pollutants (NRC 2000;Ekperusi and Aigbodion 2015), which are biohazards and biomagnified in the environment (Kramer and Van der Heijden 1990;Mohamed et al 2006). While, there are special group of microorganisms that can biodegrade and biotransform these hydrocarbons and alkanes to assimilate as biomass in the ecosystem (Chikere et al 2012;Rajasekar et al 2012;Roy et al 2015;Kumar et al 2016). However, few alkanes are recalcitrant in the environment (e.g., long chain and high molecular weight hydrocarbons) due to their non-polar and chemically inert nature (Labinger and Bercaw 2002).…”
Section: Introductionmentioning
confidence: 99%